Mindfulness Interventions for Disease Distress Symptomatology in Cancer: Review and Results - Tacón, A. M. (Highlights on Medicine and Medical Research Vol. 15, 2021)
During cancer treatment, individuals feel discomfort, which is likely to be compounded by pain at some time. Poor pain control is common among those with cancer, and the primary medical treatment is the prescription of opioid medications. The purpose here was to provide a review as well as to investigate the efficacy of a modified eight-week mindfulness-based intervention on the pain-related factors of pain anxiety, pain catastrophizing, symptoms of distress, and fatigue in 57 women diagnosed with breast cancer and consequent pain. As predicted, statistical analyses of pre-post scores revealed significant improvements for pain anxiety and pain catastrophizing following the eight-week intervention. Also, symptoms of distress and fatigue improved significantly pre-to-post in this group of women. These preliminary findings are encouraging, yet they must be viewed with caution until further research is conducted in this area. Hopefully, this line of research eventually will be able to provide options other than narcotics to those in pain. The bottom line is that individuals living with a life-threatening disease need complementary medicine options other than narcotics to help them deal with their pain and suffering.